Combined Effect of Cinnamon Essential Oil and Pomegranate Peel Extract on Antioxidant, Antibacterial and Physical Properties of Chitosan Films - Yuan, Gaofeng; Lv, Hua; Zhang, Yanling; Sun, Haiyan; Chen, Xiaoe (FOOD SCIENCE AND TECHNOLOGY RESEARCH, 2016)
The chitosan-based active films were developed by incorporation of cinnamon essential oil (CEO, 10 g/L), pomegranate peel extract (PPE, 10 g/L) and CEO (10 g/L) + PPE (10 g/L) and their physical, antioxidant and antibacterial properties were investigated. Incorporation of CEO and CEO + PPE into the films significantly decreased the water vapor permeability. Incorporation of CEO, PPE and CEO + PPE into the films decreased the transparency, but significantly increased the antioxidant activity. Incorporation of CEO and CEO + PPE exhibited significant antibacterial activity against Escherichia coli and Staphylococcus aureus. In addition, the antibacterial activity against the Staphylococcus aureus in the film incorporated with CEO and PPE was significantly higher than that incorporated with CEO or PPE alone, suggesting that there is a synergistic action between CEO and PPE.